Corporate social performance (csp): an experience of Bank Islam Malaysia Berhad - Muhamat, Amirul Afif; Jaafar, Mohamad Nizam; Abd Rashid, Muhammad Hafiz; Hendrayati, Heny (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
This research explores the sustainability of Islamic corporate social responsibilities (CSR) programs through the case study of bank Islam Malaysia berhad's sadaqa house platform. interviews with the key beneficiaries who are also the key informants for this study were selected based on their experiences when receiving the financial assistance. they revealed that focused csr initiatives led to enhanced satisfaction and quality of life. despite a small sample size, the study achieved its objectives due to the relevance of selected informants. this research contributes to understanding the impact and sustainability of CSR programs within financial institutions, particularly in emerging markets. bank Islam’s experience offers a valuable benchmark for best practices